2014
DOI: 10.1073/pnas.1321417111
|View full text |Cite
|
Sign up to set email alerts
|

Pilus hijacking by a bacterial coaggregation factor critical for oral biofilm development

Abstract: The formation of dental plaque, a highly complex biofilm that causes gingivitis and periodontitis, requires specific adherence among many oral microbes, including the coaggregation of Actinomyces oris with Streptococcus oralis that helps to seed biofilm development. Here, we report the discovery of a key coaggregation factor for this process. This protein, which we named coaggregation factor A (CafA), is one of 14 cell surface proteins with the LPXTG motif predicted in A. oris MG1, whose function was hitherto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 26 publications
8
70
0
Order By: Relevance
“…There are several limitations inherent to the mechanical study of purified pili. Pili do not exclusively contain the SpaA shaft proteins, and measurements may be confounded by incorporated adhesins and other ancillary proteins (13). Moreover, the attachment of pili to the surface and cantilever relies on nonspecific interactions, such that the vector of the force is not explicitly defined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several limitations inherent to the mechanical study of purified pili. Pili do not exclusively contain the SpaA shaft proteins, and measurements may be confounded by incorporated adhesins and other ancillary proteins (13). Moreover, the attachment of pili to the surface and cantilever relies on nonspecific interactions, such that the vector of the force is not explicitly defined.…”
Section: Resultsmentioning
confidence: 99%
“…3E). The native FimA pili of A. oris measure 1-2 μm in length, the equivalent of ∼140-280 pilins polymerized in series, each ∼7 nm from the intermolecular cross-link to the C terminus (13). Without unfolding, such as in the CnaB Spy0128-type pilus of S. pyogenes, force extension follows a worm-like chain contour that rises unimpeded into the nanonewton range, where the lifetimes of covalent bonds are brief (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this approach, we could avoid the formation of high-molecular-weight (HMW) glycosylated GspA by forcing the protein to be released as a monomer to facilitate the detection of small changes in preprotein processing. After harvesting of the cell-free culture supernatants of A. oris strains expressing this construct by centrifugation and filtration, His-tagged proteins were captured by Ni-nitrilotriacetic acid agarose and purified according to a previously published protocol (7). Purified proteins were analyzed by SDS-PAGE and then Coomassie blue and periodic acid-Schiff (PAS) staining (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Type 2 fimbriae-composed of the shaft fimbrillin FimA and the tip fimbrillin FimB-promote polymicrobial interactions or bacterial coaggregation, biofilm formation, and adhesion to host cells (2,5,6). A. oris also encodes 14 cell wall-anchored proteins (AcaA to AcaN), one of which, CafA (previously named AcaF), has been shown to be the major coaggregation factor that forms a distinct fimbrial tip of type 2 fimbriae (7). It was recently shown that the cell wall-anchored protein AcaC (named GspA) is glycosylated, and its glycosylation appears to be coupled to protein secretion and sortase SrtA-catalyzed cell wall anchoring (8).…”
mentioning
confidence: 99%